Enhancement of Prognostic Outcomes in Stage III Non-Small Cell Lung Cancer: A Retrospective Study on Neoadjuvant Immuno-Chemotherapy Followed by Definitive Chemo-Radiotherapy - Wenxin Ding; Yechen Ma; Hao Hu; Tian Xu; Hexin Duan; Jing Liang; Weiwei Liang; Hao Zhou; Xi Zhang; Zewen Song (Translational Oncology)
Background: The effectiveness of neoadjuvant immuno-chemotherapy in stage III non-small cell lung cancer (NSCLC) patients undergoing definitive concurrent/sequential chemo-radiotherapy (CRT) is not well established. Methods: This retrospective study involved stage III NSCLC patients treated at the Third Xiangya Hospital and Xiangxi Autonomous Prefecture People's Hospital. We compared prognosis, dosimetric outcomes, and radiation pneumonitis incidence between those receiving neoadjuvant immuno-chemotherapy and those undergoing immunotherapy maintenance after CRT. Tumor assessments were conducted on patients administered 2–4 cycles of immuno-chemotherapy, and diagnostic CT images of 54 patients were analyzed for treatment impact. Results: A total of 76 patients received neoadjuvant immuno-chemotherapy followed by CRT, while 68 received immunotherapy after CRT. The median progression-free survival (PFS) for the neoadjuvant group was 29.3 months compared to 13.4 months for the maintenance group (p < 0.001). Median overall survival (OS) was not reached for the neoadjuvant group, while it was 37.4 months for the maintenance group (p = 0.004). Uni-variable analysis indicated neoadjuvant immuno-chemotherapy as an independent OS prognostic factor. The disease control rate was 99.09 %, and significant reductions in tumor volume and radiation doses to healthy tissues were observed post-treatment. Conclusion: Our findings suggest neoadjuvant immuno-chemotherapy improves prognosis for stage III NSCLC patients and effectively reduces tumor volume and organ-at-risk radiation exposure, warranting further phase III trials.